An exploration into the cortical reorganisation of the healthy hand in upper-limb complex regional pain syndrome - Pietro, Flavia; Stanton, T.R.; Moseley, G.L.; Lotze, M.; McAuley, J.H. (2017)
© 2016 Scandinavian Association for the Study of Pain.